NAGAS AS OTHERS: EXHUMING THE DESPOTIC COUNTERINSURGENCY OF THE INDIAN ARMY AND EXPLICATING ITS PROVOCATIONS THROUGH EASTERINE KIRE’S BITTER WORMWOOD - K., Nithya; Albert, Anita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tribal literature is a phenomenal literary branch in the abode of literature as it represents the lives of the original inhabitants of a particular soil, which are predominantly enswathed with catastrophic predicaments as they are discriminated and subjugated in their own lands. The writers of Tribal literature strive to unveil the true state of tribal life, which is hidden behind the numerous screens of misinterpretation throughout history, and to prop up the tribal stand by unearthing reality. They depict the salient ethnic history, culture, and tradition of all the tribal communities, along with the threats to all these prominent components. They articulate their voices through their paramount skill of writing for the unheard, underrepresented, and misrepresented voices of the tribal people. Easterine Kire is one such admirable writer from Nagaland who constantly unravels the misapprehended lives of Nagas by having them as the marrow of her literary contributions. Bitter Wormwood is her most influential novel, in which she composites the history of Naga insurgency and counterinsurgency with some fictional incidents to publicise how the Naga tribes as well as the Indian army endured that cataclysmic movement. Through scrutinising this novel, the researcher diagnoses why the Indian army whose obligation is to protect Indians, besieges and excruciates the Nagas, and why this despotic counterinsurgency is not divulged. Subsequently, the present article intends to demonstrate the hypothesis that Nagas are treated as ‘others’ rather than Indians throughout the counterinsurgency of the Indian army.